Observation-based anthropogenic carbon estimates in the Arctic Ocean ... - Terhaar, Jens; Tanhua, Toste; Stöven, Tim; Orr, James C; Bopp, Laurent (SEANOE, 2024)
Although the Arctic Ocean is quickly changing wih climate change and increasing atmospheric CO2, it is still relatively poorly surveyed because of logistical difficulties. Observations that allow to estimate the change in carbon due to the addition of anthropogenic carbon (Cant) are much sparser than physical oceanography observations. Although estimates of Cant are sparse, they are highly important to quantify and monitor the ongoing ocean acidification to which the Arctic Ocean is particularly vulnerable. Here, we provide Cant estimates for 2005 across all basins and depths based on transient tracer measurements (e.g., CFCs and SF6) between 1983 and 2005 (Tanhua et al., 2009). Based on the transient tracers, Cant is estimated using the transit time distribution (TTD) concept. We further provide adjusted Cant estimates for 2005 (Terhaar et al., 2020). This adjustment corrects the original Cant estimates upward by accounting for a bias that results from the idealized assumption of gas equilibrium between ...